Soil fertility assessment of Hanumante sub-watershed at Suryabinayak municipality of Bhaktapur district - Dahal, Mallika; Pandit, Naba R; Ojha, Roshan B (Nepal Agriculture Research Journal, 2025)
Soil fertility assessment is critical for enhancing land productivity and ensuring sustainability of agricultural systems. An evaluation at the sub-watershed scale is lacking in Nepal. This research was carried out to assess the soil fertility status of Hanumante sub-watershed at Suryabinayak municipality of Bhaktapur district in June 2024 prior to the onset of the monsoon rain. A total of 30 composite soil samples were collected from the study area, representing two altitudinal land types (upland and lowland). These samples were collected from the field of 30 local farmers to assess soil fertility in conjunction with the household survey to understand their fertility management practices. Data was analyzed in SPSS using descriptive statistics and cross-tabulation between the soil fertility and fertility management practices. Findings revealed that predominant soil textural class in the sub-watershed was silty loam (70%), soil pH was moderately acidic (average pH 5.75), soil OM and total N were at 'medium' levels with average contents of 3.44% and 0.18%, available P and K were at 'high' and 'very high' levels with average of 348 kg/ha and 363 kg/ha and soil Ca and Mg were also at 'high' levels with average contents of 14,683 ppm and 1,189 ppm, respectively. Farmer-reported crop yields were relatively high in the lowland areas. However, the yields of maize and rice, as observed by farmers, declined by 50% in the last 10 years across both lowland and upland areas. Correlation analysis using a linear regression model showed no significant relationship (p < 0.05) between soil nutrients and farmer-reported crop yields. Most farmers have consistently used the same quantities of inorganic fertilizers for years with limited soil fertility management knowledge. These findings help farmers understand and make site-specific precision fertilizer management and support stakeholders in formulating effective strategies for ensuring soil health and sustainable soil fertility management in the study area.